Parents’ Perceptions of School Support During COVID-19: What Satisfies Parents? - Haller, Teresa; Novita, Shally (Frontiers in Education, 2021)
During the COVID-19 pandemic lockdown, face-to-face schooling could not be performed continuously, and alternative ways of learning had to be organized. Parents had to act as their children’s home schooling tutors while working from home, and schools had to deal with various alternatives to distance education. Since parents are by all means both important school users and partners, their perceptions of schools can be considered a central indicator for assessing school quality. In this respect, during school lockdown, parents’ school satisfaction may reflect schools’ ability to adjust and react to fast social changes with almost no time for preparation. To date, there is nearly no knowledge about school satisfaction or school support during this challenging situation. Using data from the COVID-19 survey of the German National Educational Panel Study, we identified central predictors of parents’ perceptions of school support during the national lockdown in Germany in spring 2020. All students (N = 1,587; Mage = 14.20; SD = 0.36; 53% girls) and their parents (Mage = 47.36; SD = 4.99; 91% women) have participated in the longitudinal survey for at least 8 years. The results of the structural equation model indicate that the perceived support and abilities of teachers have been especially relevant for parents’ school satisfaction during the time of the school lockdown. In contrast, factors relating to parents’ and children’s backgrounds seem to be less important.